1983
DOI: 10.1002/jnr.490100306
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of 3H‐valine into soluble protein of cultivated astroglial cells after morphine treatment

Abstract: Uptake and incorporation of 3H-valine into soluble protein of cultivated astroglial cells from newborn rat cerebral hemispheres increased after incubating the cells for 4 hr in 10(-6) or 10(-5) M morphine. The effects, inhibited by high naloxone concentrations, were not mediated by cyclic adenosine monophosphate (cAMP)-activated binding sites for morphine or D-alanine2-methionine-enkephalin-amide (D-ala2-met-enk-amide). The cultures consisted of 60-70% astrogliallike cells. By changing the kinetics of labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For example, Hansson and Rönnbä ck (1983) reported significant opioid effects on protein synthesis in astrocyte cultures in the absence of classic morphine binding sites. Rönnbä ck and Hansson (1985) and Hansson and Rönnbä ck (1985) continued this discussion of the role of astrocytes in the development of opioid tolerance, suggesting that the synthesis of proteins that is required for the development of tolerance and physical dependence are not related to the opioid receptor actions.…”
Section: The Clinical Predicament Of Ineffective Opioid Analgesia Andmentioning
confidence: 99%
“…For example, Hansson and Rönnbä ck (1983) reported significant opioid effects on protein synthesis in astrocyte cultures in the absence of classic morphine binding sites. Rönnbä ck and Hansson (1985) and Hansson and Rönnbä ck (1985) continued this discussion of the role of astrocytes in the development of opioid tolerance, suggesting that the synthesis of proteins that is required for the development of tolerance and physical dependence are not related to the opioid receptor actions.…”
Section: The Clinical Predicament Of Ineffective Opioid Analgesia Andmentioning
confidence: 99%
“…The use of 3H-valine allows only the assessment of aminoacid incorpo ration into proteins. Hansson and Ronnback [33] have shown that 3H-valine incorporation into astrocyte protein is linear. In our experiments incorporation time was 3 h. Moreover, 3 uCi of 3H-valine added to each Petri dish were found to be the optimum.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were incubated with 3 pCi/dish (4 ml) of L-[3. 4-'H]-valine (57.3 Ci/mmol) for 3 It in serum-free DMEM [33], The incubation was terminated by aspiration of the medium and astrocytes were rinsed twice with ice-cold Grey's balanced salt solution [34], Cells were scraped from the dishes with a plastic policemann (Costar. Co, Cambridge, Mass.)…”
Section: Protein Incorporation O F -Valinementioning
confidence: 99%